Structure and algorithm for adaptive control of machining process - Trần Văn Khiêm (Journal of Technical Education Science, 2019)
Adaptive Control (AC) is an intelligent and flexible control solution which has the capability of self-adapting to uncertainties in inputs, system parameters and the environment. In machining technology, the application of AC is the inevitable trend of CNC. However, in order to be able to design AC systems that meet the requirements of the industry, it is necessary to solve the key problems of system architecture, control algorithms as well as measurement, control and coupling AC with CNC. This paper presents the structure and algorithm of the AC, that have been developed, improved and tested on CNC milling machine for recent years. Testing results show that this AC is capable of on-line adjusting the feed rate against abnormal cutting depth variations and allows to increase the machining productivity of 25% compared to CNC without AC while still ensuring the process quality.